Thermoelectric cement base meeting low-grade heat energy thermoelectric power generation requirement

By introducing ionic liquids in the pores of the cement matrix, the use of temperature difference field and entropy difference can make the ion free radicals in the ionic liquid occur orientation, realize the thermal power conversion effect, solve the high cost of the existing thermoelectric cement base materials and the low thermal power performance The problem has achieved the effect of low -quality thermal temperature difference.

CN119330649AActive Publication Date: 2025-01-21SICHUAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411457502.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing thermoelectric cement-based materials have high economic costs and low thermoelectric properties, making it difficult to output sufficient voltage under low grade temperature differences.

Method used

By introducing ionic liquids with differences in internal ion entropy in the pores of the cement matrix, the combined effect of the temperature difference field and entropy difference can be used to make the ion free radicals in the ionic liquid occur directional migration and achieve the thermal power conversion effect.

Benefits of technology

The SEEBECK coefficient of the thermoelectric cement base is significantly improved, ensuring that sufficient voltage is output under the conditions of low -quality temperature differences, meet the requirements of low -quality thermal energy temperature difference power generation, and reduce the preparation cost of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330649A_ABST
    Figure CN119330649A_ABST
Patent Text Reader

Abstract

The invention discloses a thermoelectric cement base meeting the requirement of low-grade heat energy thermoelectric power generation, and relates to the technical field of thermoelectric cement base materials, the thermoelectric cement base comprises an ionic liquid internally having an ion entropy difference and a cement base body serving as a bearing structure, and the cement base body is internally provided with a plurality of mutually communicated pores; the ionic liquid is introduced into pores of the cement matrix; the ionic liquid is thermoelectric effect ionic liquid or anion-cation pair liquid with Sore effect; when the thermoelectric cement base is connected with an external load, a temperature difference field is formed at two ends of the thermoelectric cement base, and ion free radicals in the ionic liquid are directionally migrated in pores under the combined action of the temperature difference field and entropy difference, so that the cement base generates a thermoelectric conversion effect, and thermoelectric power generation is realized. The thermoelectric cement-based material can meet the low-grade thermoelectric power generation requirement without doping expensive semiconductor materials, the preparation cost is low, and basic guarantee can be better provided for construction, operation and popularization of a large-scale clean energy power plant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermoelectric cement-based materials, and in particular to a thermoelectric cement-based material that meets the requirements for low-grade thermal energy temperature difference power generation. Background Art

[0002] Faced with increasingly serious environmental pollution and shortage of traditional energy (such as oil and natural gas), modern society has a growing demand for clean energy technology. However, building large-scale clean energy power plants requires high costs and occupies a large area of ​​land, which has a high threshold. In addition, the large area also makes it impossible to build in densely populated urban areas, so long-distance transmission and distribution facilities are required to complete power transmission, which brings higher electricity costs.

[0003] As one of the most widely used building materials, cement-based materials are cheap and have a large stock size. At present, some studies have been conducted on the thermoelectric effect of cement-based materials. The thermoelectric effect generated by the temperature difference of cement-based materials can convert thermal energy into electrical energy. In addition, traditional power generation methods are difficult to effectively utilize low-grade thermal energy, resulting in the waste of this part of resources. The use of the thermoelectric effect of cement-based materials can well realize the utilization of low-grade thermal energy, which not only makes up for the shortcomings of traditional power generation methods, but also the effective use of low-grade thermal energy can reduce energy consumption and save costs (for example, using the electricity converted from low-grade thermal energy to provide working power for some signal detection systems), which also provides more possibilities for the construction, operation and promotion of clean energy power plants.

[0004] For thermoelectric cement-based materials, most of the previous studies are based on doping semiconductor materials such as carbon nanotubes, nano-carbon black, and nano-graphene to achieve thermoelectric effect. For example, Patent Publication No. ES2908123R1 discloses a thermoelectric conductive cement mortar doped with graphite and graphene nanomaterials.

[0005] However, the economic cost of the above-mentioned thermoelectric cement-based materials is extremely high, making it difficult to achieve large-scale application. In addition, due to the inherent characteristics of the semiconductor thermoelectric effect, the thermoelectric performance achieved by the above-mentioned thermoelectric cement-based materials is relatively low, and the Seebeck coefficient is mostly in the order of 10 to 1000 μV / k. Therefore, it is difficult to output sufficient voltage under low-grade temperature difference conditions. Summary of the invention

[0006] In view of the above-mentioned deficiencies of the prior art, the present invention provides a thermoelectric cement-based material that can meet the requirements of low-grade temperature difference power generation.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation, comprising an ionic liquid with ion entropy difference inside and a cement matrix as a bearing structure, wherein the cement matrix has a plurality of interconnected pores inside, and the ionic liquid is introduced into the pores of the cement matrix; the ionic liquid is a thermoelectric effect ionic liquid or an anion-cation pair liquid with Soret effect; when the thermoelectric cement base is connected to an external load, a temperature difference field is formed at both ends of the thermoelectric cement base, and under the combined action of the temperature difference field and the entropy difference, the ion free radicals in the ionic liquid migrate directionally in the pores, so that the cement matrix produces a thermoelectric conversion effect, thereby realizing temperature difference power generation.

[0009] Preferably, the thermoelectric effect ionic liquid is a mixed solution containing potassium ferrocyanide and potassium ferrocyanide.

[0010] Furthermore, the thermoelectric effect ionic liquid also contains potassium chloride.

[0011] Preferably, in the thermoelectric effect ionic liquid, the volume molar concentration ratio of potassium ferrocyanide, potassium ferrocyanide and potassium chloride is 0.15-0.3:0.25-0.5:0.8.

[0012] Furthermore, in the thermoelectric effect ionic liquid, the volume molar concentration ratio of potassium ferrocyanide, potassium ferrocyanide and potassium chloride is 0.25:0.42:0.8.

[0013] Preferably, the anion-cation pair liquid having the Soret effect is any one of potassium chloride, sodium chloride and potassium sulfate.

[0014] Furthermore, the anion-cation pair liquid having the Soret effect is 0.8M potassium chloride, or 0.8M sodium chloride, or 0.4M potassium sulfate.

[0015] Preferably, the cement matrix is ​​made of any one of pure paste, mortar and concrete.

[0016] Furthermore, a sealing wrapping layer is also provided outside the cement matrix.

[0017] Preferably, the sealing wrapping layer is any one or more of resin, waterproof coating, and waterproof membrane.

[0018] The design principle of the present invention is as follows:

[0019] Introduce ionic liquid into the pores of cement matrix, and make use of the widely existing interconnected pores in cement-based materials to make the ionic liquid interconnected in the cement matrix. In this way, when there is a temperature difference between the two ends of the thermoelectric cement matrix, under the action of the temperature difference field, the ionic free radicals (positive and negative ions with charges) inside the ionic liquid will migrate in a directional manner in the pores of the cement matrix due to their own entropy difference, thereby realizing the ionic thermoelectric effect.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention combines the pores of the cement-based material itself to introduce an ionic liquid with an ion entropy difference inside, and connects an external load so that the thermoelectric cement-based material and the external load form a loop. In this way, when there is a temperature difference at both ends of the thermoelectric cement-based material, under the action of the temperature difference field, due to the existence of the entropy difference, the ion free radicals inside the ionic liquid will migrate in a directional manner in the pores, thereby generating an ion thermoelectric effect, and realizing the thermoelectric power generation of the cement-based material. Therefore, the method of realizing thermoelectric power generation using thermoelectric cement-based materials of the present invention has the characteristics of ingenious design, simple operation, and high compatibility with multiple types of building facilities.

[0022] (2) The ionic liquid in the present invention is a composite solution of potassium ferrocyanide and potassium ferrocyanide (thermoelectric effect ionic liquid). Under the action of the temperature difference field, the ferrocyanide ions at the high temperature end are oxidized to ferrocyanide ions, and release electrons to enter the external load, and the formed ferrocyanide ions migrate to the low temperature end; while the ferrocyanide ions at the low temperature end are reduced to ferrocyanide ions, and receive electrons input from the external load, and the formed ferrocyanide ions migrate to the high temperature end. In this cycle, the thermoelectric power generation of cement-based materials can be realized.

[0023] In addition, potassium chloride is further added to the ionic liquid of the present invention. Chloride ions and potassium ions form a double electric layer at the electrode site, so that electrons / holes with opposite charges are on the electrode, thereby further increasing the potential difference between the two electrodes, which can further enhance the thermoelectric effect of ferrocyanide ions and ferrocyanide ions.

[0024] In addition, in addition to the composite solution of potassium ferrocyanide and potassium ferrocyanide, the ionic liquid in the present invention can also be an anion-cation pair liquid with Soret effect, such as potassium chloride, sodium chloride, potassium sulfate, etc.

[0025] Experiments show that the Seebeck coefficient of the ionic liquid + temperature difference power generation method of the present invention is improved by at least one order of magnitude compared with existing thermoelectric cement-based materials, ensuring sufficient voltage output under low-grade temperature difference conditions to meet the requirements.

[0026] (3) The present invention also provides a sealing wrapping layer outside the cement matrix, which can prevent the evaporation of water in the ionic liquid in the atmospheric environment, and further ensure the temperature difference power generation of the thermoelectric cement-based material.

[0027] (4) The present invention can make the thermoelectric cement-based material meet the requirements of low-grade temperature difference power generation without doping with expensive semiconductor materials. Not only is the preparation cost low, but the external load only needs to have the ability to transmit electrons to make the thermoelectric cement-based material produce thermoelectric effect. Therefore, the present invention can better provide a basic guarantee for the construction, operation and promotion of large-scale clean energy power plants. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the introduction of ionic liquid into the pores of the cement matrix in Example 1 of the present invention.

[0029] Figure 2 This is a schematic diagram of the power generation principle of the thermoelectric cement-based power plant in Example 3 of the present invention. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with various embodiments and drawings. The embodiments of the present invention include but are not limited to the following embodiments.

[0031] Example 1

[0032] This embodiment provides a thermoelectric cement-based material specially adapted for low-grade thermal energy temperature difference power generation, which uses a cement matrix as a bearing structure and introduces ionic liquid into the abundant pores inside the cement matrix to obtain the target thermoelectric cement-based material. The specific production method is as follows:

[0033] First, a cement matrix and an ionic liquid are prepared separately. The cement matrix in this embodiment is made of mortar, and the interior of the prepared cement matrix has a rich pore structure; the ionic liquid is a mixed solution containing potassium ferrocyanide and potassium ferrocyanide, and the volume molar concentration ratio of potassium ferrocyanide to potassium ferrocyanide is 0.25:0.42.

[0034] After preparing the cement matrix and the ionic liquid, the cement matrix is ​​immersed in the ionic liquid by an infiltration method, so that the ionic liquid can be introduced into the pores of the cement matrix. On this basis, the vacuum saturation technology can also be combined to increase the absorption of the cement matrix to the ionic liquid. Figure 1 This is the situation after the ionic liquid is introduced into the pores of the cement matrix.

[0035] The above-mentioned thermoelectric cement base can be used as the basic material of various building facilities, for example, as a wall surface, connected to an external load, so that the two form a loop. When there is a temperature difference between the inside and outside of the wall, due to the entropy difference between ferrocyanide ions and ferrocyanide ions, the two will migrate to the low temperature end and the high temperature end respectively under the action of the temperature difference field. Specifically, on the high temperature side, ferrocyanide ions are oxidized to ferrocyanide ions, and release electrons to enter the external load, and the formed ferrocyanide ions migrate to the low temperature side; on the low temperature side, ferrocyanide ions are reduced to ferrocyanide ions, and obtain electrons input from the external load, and the formed ferrocyanide ions migrate to the high temperature side, thereby generating a thermoelectric effect and providing electrical energy for the external load.

[0036] Example 2

[0037] The difference from Example 1 is that potassium chloride is also added to the ionic liquid in this example, and the volume molar concentration ratio of potassium ferrocyanide, potassium ferrocyanide and potassium chloride is 0.25:0.42:0.8. In this example, the method of forming a double electric layer at the electrode site by chloride ions and potassium ions can make the electrodes have electrons / holes with opposite charges, thereby further increasing the potential difference between the two electrodes, so as to further enhance the thermoelectric effect of ferrocyanide ions and ferrocyanide ions. Figure 2 The power generation principle of the thermoelectric cement-based power generation system of this embodiment is demonstrated.

[0038] Example 3

[0039] The difference from Example 2 is that in this example, the volume molar concentration ratio of potassium ferrocyanide, potassium ferrocyanide and potassium chloride is 0.3:0.5:0.8.

[0040] Example 4

[0041] The difference from Example 2 is that in this example, the volume molar concentration ratio of potassium ferrocyanide, potassium ferrocyanide and potassium chloride is 0.15:0.25:0.8.

[0042] Example 5

[0043] The difference from Example 1 is that in this example, the ionic liquid is 0.8M (volume molar concentration) potassium chloride. Under the action of the temperature difference field and the Soret effect, the carriers in the potassium chloride solution migrate in a directional manner, which can generate a thermoelectric effect and provide electrical energy for the external load.

[0044] Example 6

[0045] The difference from Example 1 is that in this example, the ionic liquid is 0.8M (volume molar concentration) sodium chloride. Under the action of the temperature difference field and the Soret effect, the ions in the sodium chloride migrate in a directional manner, which can generate a thermoelectric effect and provide electrical energy for the external load.

[0046] Example 7

[0047] The difference from Example 1 is that in this example, the ionic liquid is 0.4M (volume molar concentration) potassium sulfate. Under the action of the temperature difference field and the Soret effect, the ions in the potassium sulfate migrate in a directional manner, which can generate a thermoelectric effect and provide electrical energy for the external load.

[0048] Example 8

[0049] The difference from Example 1 is that in order to prevent the evaporation of moisture in the thermoelectric cement base and affect the thermoelectric effect of the thermoelectric cement base, this embodiment also provides a sealing wrapping layer on the outside of the cement base. The sealing wrapping layer can be made of a series of materials such as resin, waterproof coating, waterproof roll material, etc. to lock the moisture in the thermoelectric cement base.

[0050] Example 9

[0051] This embodiment provides an experimental device to verify the voltage and Seebeck coefficient of the thermoelectric cement-based thermoelectric effect of embodiments 1-7.

[0052] 1. Experimental Preparation

[0053] Cement matrix: Cement mortar samples with a water-cement ratio of 0.7 were prepared, and the specimen size was 40*40*30mm.

[0054] Ionic liquid: The corresponding ionic liquids were prepared according to Examples 1-7, and then the test pieces were placed in the above ionic liquids for 7 days under vacuum.

[0055] Experimental equipment and devices: constant temperature water bath, thermometer, U-shaped clamp, high-precision digital multimeter, copper water cooling head, graphite electrode, insulating thermal conductive silicone pad and thermocouple.

[0056] The above equipment is mainly divided into three parts: temperature control system, voltage measurement system and fixed clamping equipment, among which:

[0057] Temperature control system: First, use a constant temperature water bath to maintain the water temperature in the pot at 30.2℃ and 65.0℃ respectively (considering the heat loss during the water pipe transmission process, the water temperature in the water bath is higher than the water temperature in the water cooling head), and then use a water pump to pump water of different temperatures into the copper water cooling head, so that the two water cooling heads are maintained at 30℃ and 60℃ respectively, and the temperature of the water cooling head is monitored in real time by connecting the thermometer through a thermocouple.

[0058] Voltage measurement system: A graphite electrode sheet and an insulating thermally conductive silicone pad are respectively set between the specimen and the copper water-cooling head. The graphite electrode sheet serves as an electrode to collect charges and transmit the potential difference between the two ends of the specimen to a high-precision digital multimeter through a wire. A silicone pad is used to prevent the graphite electrode from being conductive to the copper water-cooling head. At the same time, considering the good thermal conductivity and small thickness of the graphite sheet and the silicone pad, the heat loss caused by the graphite electrode sheet and the silicone pad is ignored, that is, the temperature at both ends of the specimen is considered to be consistent with the temperature of the copper water-cooling head.

[0059] Clamping system: The water cooling head, silicone pad, graphite electrode and test piece are clamped and fixed by U-shaped clamps to ensure good contact.

[0060] 2. Experimental process

[0061] STEP1: Turn on two constant temperature water baths and water pumps, and adjust the target temperatures respectively. Monitor the thermometer readings. When the readings stabilize at 30℃ (303.15K) and 60℃ (333.15K), the target temperature of the constant temperature water baths can be considered to have met the experimental requirements.

[0062] STEP2: Turn on and connect the digital multimeter, clamp the test piece in the test sequence fixed by the U-shaped clamp, start measuring the voltage, and record the voltage signal with a computer. Considering the large specific heat capacity of water and the large amount of water in the temperature control system, the heat exchange between the water cooling head and the test piece has almost no effect on the water temperature.

[0063] STEP 3: When the voltage change is less than 1mV / min, it is considered to have reached a steady state, and the voltage at the steady state is recorded as the final output voltage.

[0064] 3. Experimental results

[0065] The relevant experimental results of Examples 1-7 are shown in Table 1:

[0066] plan Voltage / mV Seebeck coefficient / mV·k-1 Example 1 366.12 11.85 Example 2 421.06 14.04 Example 3 257.16 8.57 Example 4 64.95 2.16 Example 5 82.22 2.74 Example 6 139.24 4.64 Example 7 112.57 3.75

[0067] Table 1

[0068] Table 2 shows the test results of the test pieces (the size of the test pieces is 40*40*30 mm) prepared with a water-cement ratio of 0.5 and then subjected to vacuum saturation in the ionic liquid of Example 2 for 7 days.

[0069] plan Voltage / mV Seebeck coefficient / mV·k-1 Example 2 94.57 3.15

[0070] Table 2

[0071] Table 3 shows the test results of the test pieces (the size of the test pieces is 40*40*30 mm) prepared with a water-cement ratio of 0.6 and then subjected to vacuum saturation in the ionic liquid of Example 2 for 7 days.

[0072] plan Voltage / mV Seebeck coefficient / mV·k-1 Example 2 263.03 8.77

[0073] Table 3

[0074] According to the results in Tables 1-3, in the cement matrix prepared with a water-cement ratio of 0.5-0.7, the Seebeck coefficients of Examples 1-7 are between 2.16 mV / k and 14.04 mV / k. Therefore, the solution adopted in the present invention improves the Seebeck coefficient by one order of magnitude compared with the existing solution.

[0075] The present invention seems simple, but it is not easy to think of. Only by deeply studying the thermoelectric effect principle of cement-based materials and combining the characteristics of related materials can we design a thermoelectric cement-based material that can meet the requirements of low-grade thermal energy temperature difference power generation in a simple and effective way, and greatly reduce the preparation cost of thermoelectric cement-based materials, and better provide basic guarantees for the construction, operation and promotion of large-scale clean energy power plants. Therefore, compared with the existing technology, the present invention has obvious technical progress, outstanding substantive characteristics and significant progress.

[0076] The above embodiments are only preferred implementation modes of the present invention and should not be used to limit the protection scope of the present invention. Any changes or modifications that are made to the main design concept and spirit of the present invention and have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention.

Claims

1. A thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation, characterized in that: It includes an ionic liquid with ion entropy difference inside and a cement matrix as a bearing structure, wherein the cement matrix has a plurality of interconnected pores inside, and the ionic liquid is introduced into the pores of the cement matrix; the ionic liquid is a thermoelectric effect ionic liquid or an anion-cation pair liquid with Soret effect; when the thermoelectric cement base is connected to an external load, a temperature difference field is formed at both ends of the thermoelectric cement base, and under the combined action of the temperature difference field and the entropy difference, the ion free radicals in the ionic liquid migrate directionally in the pores, so that the cement matrix produces a thermoelectric conversion effect, thereby realizing temperature difference power generation.

2. The thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation according to claim 1 is characterized in that: The thermoelectric effect ionic liquid is a mixed solution containing potassium ferrocyanide and potassium ferrocyanide.

3. The thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation according to claim 2 is characterized in that: The thermoelectric effect ionic liquid also contains potassium chloride.

4. The thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation according to claim 3 is characterized in that: In the thermoelectric effect ionic liquid, the volume molar concentration ratio of potassium ferrocyanide, potassium ferrocyanide and potassium chloride is 0.15-0.3:0.25-0.5:0.

8.

5. The thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation according to claim 4 is characterized in that: In the thermoelectric effect ionic liquid, the volume molar concentration ratio of potassium ferrocyanide, potassium ferrocyanide and potassium chloride is 0.25:0.42:0.

8.

6. The thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation according to claim 1, characterized in that: The anion-cation pair liquid having the Soret effect is any one of potassium chloride, sodium chloride and potassium sulfate.

7. The thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation according to claim 6 is characterized in that: The anion-cation pair liquid having the Soret effect is 0.8M potassium chloride, or 0.8M sodium chloride, or 0.4M potassium sulfate.

8. A thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation according to any one of claims 1 to 7, characterized in that: The cement matrix is ​​made of any one of pure paste, mortar and concrete.

9. The thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation according to claim 8, characterized in that: A sealing wrapping layer is also provided outside the cement matrix.

10. The thermoelectric cement base that meets the requirements of low-grade thermal energy temperature difference power generation according to claim 9, characterized in that: The sealing wrapping layer is any one or more of resin, waterproof coating and waterproof coiled material.

Citation Information

Patent Citations

  • Dapaded cement mortars with graffiti and graphenic nanomaterials with thermoelectric conduction

    ES2908123A2

  • Cement-based composite with thermoelectric power generation characteristic

    CN109608138A

  • Cement-based thermoelectric material and preparation method and application thereof

    CN116102310A

  • Cement and production thereof and concrete made therefrom

    EP0437324A2

  • Method for manufacturing coal-based geopolymer foam including silica fume

    US20230202923A1